An assessment on performance, emission and combustion characteristics of single cylinder diesel engine powered by Cymbopogon flexuosus biofuel. (1st June 2016) - Dhinesh, B.; Isaac JoshuaRamesh Lalvani, J.; Parthasarathy, M.; Annamalai, K.
Highlights: Cymbopogon Flexuosus biofuel is used as an alternative energy source. Cymbopogon flexuosus biofuel 20% + Diesel 80% blend profile stayed close to diesel. Resulting in higher thermal efficiency and reduced fuel consumption. Reduced hydrocarbon, carbon monoxide and smoke emission. Oxides of nitrogen and carbon di-oxide emission was marginally higher. Abstract: The novelty of this manuscript is that it discusses about the experimental analysis of a new biofuel feedstock as an alternative fuel that has not drawn much attention among the researchers. An exploration for a new biofuel feedstock resulted in Cymbopogon flexuosus as an alternative energy source. Raw oil of Cymbopogon flexuosus was obtained through steam distillation process. Cymbopogon flexuosus biofuel was blended with diesel fuel in various proportions on volume basis, namely 10, 20, 30, 40, and 100 percent and its properties were assessed according to American Society for Testing and Materials standards. The considered test fuel was experimentally analysed in a single cylinder diesel engine at 1500 rpm for its performance, emission and combustion characteristics. Among various blends, Fuel blend of Cymbopogon flexuosus biofuel 20% + diesel 80% fuel profile stayed close to diesel fuel resulting in higher thermal efficiency and lower hydrocarbon, carbon monoxide, and smoke emission. However, oxides of nitrogen and carbon dioxide emission was marginally higher for the test fuel considered. Cylinder pressure and heat release rate curves were lower at full load condition as compared with diesel fuel. Against the grim background of fossil fuel depletion, Fuel blend of Cymbopogon flexuosus biofuel 20% + diesel 80% fuel acts as a promising alternative fuel and brings hope to the nation as well as the research world.